PENGARUH ORIENTASI KEWIRAUSAHAAN DAN MODAL SOSIAL TERHADAP BUSINESS PERFORMANCE MELALUI COMPETITIVE ADVANTAGE PADA USAHA MIKRO DI SIDOARJO - Mardiansyah, Nafi; Novie, Muhafidhah; Muzdalifah, Laily; Sholikhah, Afifatus (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to examine the influence of Entrepreneurial Orientation and Social Capital on Business Performance, with Competitive Advantage as a mediating variable, among microenterprises in Sidoarjo Regency. A quantitative approach was employed, utilizing primary data collected via a questionnaire administered to 280 respondents. The sample for this study was determined using probability sampling with a simple random sampling approach. Data analysis was conducted using PLS-SEM via SmartPLS 4. The results indicate that Entrepreneurial Orientation has a positive and significant effect on Business Performance and Competitive Advantage. Social Capital has a significant effect on Competitive Advantage, but not directly on Business Performance. Competitive Advantage has a significant effect on Business Performance and mediates the relationship between Entrepreneurial Orientation and Social Capital on Business Performance. These findings indicate that improved performance of microenterprises can be achieved through strengthening Entrepreneurial Orientation and optimizing Social Capital focused on creating Competitive Advantage.